The EFL Teachers’ Implementation of 6C Skills (Critical Thinking, Creativity, Collaboration, Communication, Citizenship, and Character) of 21st Century Skills - Bulkis, Iin; Tahir, Muhammad; Sakkir, Geminastiti (PT ARRUS Intelektual Indonesia, 2025)
This study aimed to examine the implementation of 21st-century 6C skills (Critical Thinking, Creativity, Collaboration, Communication, Citizenship, and Character) in EFL classrooms, focusing on teachers' implementation practice. The theories of this research were social constructivism by Vygotsky (1978) and language teacher cognition by Borg (2003). Data were collected through classroom observations, semi-structured interviews, and document analysis involving two experienced EFL teachers at SMPN 27 Makassar. Findings revealed that teachers systematically integrated 6C skills through three stages such as: preparation, implementation, and evaluation. Challenges included diverse student proficiency levels, time constraints, and technological limitations, which teachers addressed through strategies like mixed-ability grouping, project-based learning (PBL), and role-playing. The study recommends professional development, resource allocation, and policy support to optimize 6C skill integration in EFL instruction.